2021
DOI: 10.1101/2021.06.08.447493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementing the reuse of public DIA proteomics datasets: from the PRIDE database to Expression Atlas

Abstract: Rising numbers of mass spectrometry proteomics datasets available in the public domain, increasingly include volumes generated from Data Independent Acquisition approaches, SWATH-MS in particular. Unlike Data Dependent Acquisition datasets, their re-use is limited, partially due to challenges in combination and use of free software for analysis in the non-specialist laboratory. We introduce a (re-)analysis pipeline for SWATH-MS data available in the PRIDE database, which includes a harmonised combination of me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…After filtering out the disease and statistically insignificant pathways, there were 2,990 pathways found in all the organs of mouse and 2,162 pathways in all the organs of rat. In mouse samples, the largest number of pathways (367) were found in articular cartilage, and the lowest number of pathways was from liver (44). We also observed that Neuronal Systemrelated pathways are predominantly present in the brain and eye, which is consistent with expectations.…”
Section: Pathway Enrichment Analysissupporting
confidence: 90%
“…After filtering out the disease and statistically insignificant pathways, there were 2,990 pathways found in all the organs of mouse and 2,162 pathways in all the organs of rat. In mouse samples, the largest number of pathways (367) were found in articular cartilage, and the lowest number of pathways was from liver (44). We also observed that Neuronal Systemrelated pathways are predominantly present in the brain and eye, which is consistent with expectations.…”
Section: Pathway Enrichment Analysissupporting
confidence: 90%
“…Additionally, ten SWATH-MS DIA datasets coming mainly from cell line and human tumor samples have also already been re-analysed and integrated into Expression Atlas. In this case, an in-house open analysis pipeline based on OpenSWATH ( https://github.com/PRIDE-reanalysis/DIA-reanalysis ) was developed and used for the re-analysis ( 53 ). These datasets constituted a pilot project to study the feasibility of performing a systematic reanalysis and integration of DIA datasets.…”
Section: Pride Archive As a Hub Of Ms Evidencesmentioning
confidence: 99%
“…In this case, an in-house analysis pipeline was built using OpenSWATH as the base ( https://github.com/PRIDE-reanalysis/DIA-reanalysis ). These datasets constituted a pilot project to study the feasibility of performing a systematic reanalysis of DIA datasets and included cell-line, human cancer-related and plasma samples ( 27 ).…”
Section: Datasets and Speciesmentioning
confidence: 99%